Effect of Surface Treatment on the Bond Strength of Quartz Fiber-Reinforced Resin Posts to Resin Cements: In Vitro Study - Herrera-Ocampo DDS, MSD, Luis A. (2017)
The purpose of this study was to determine the effect of different surface treatments on the bond strength between resin cements and quartz fiber-reinforced resin posts. Materials and methods: Sixty quartz fiber-reinforced resin posts (DT Light-Post™, Bisco™) were randomly divided into 12 experimental groups (n=5), according to the resin cement used (Biscem™ or Duolink™) and the surface treatment: Alcohol (control group), silanized, primer, sandblasted, sandblasted + silanized or sandblasted + primer. Cylindrical resin specimens were obtained using nanohybrid resin. The posts were cemented to the resin discs and push-out tests were conducted. Data were analyzed with ANOVA and T test for averages comparison and the Tukey HSD test with a 95% level of significance. Results: Biscem™ cement generally showed higher bond strength when compared to Duolink™ Significant differences were found between the control group and the sandblasted + silane and sandblasted + primer groups when using Duolink™cement. With Biscem™ cement, no differences between groups or with the control group were found.. Conclusion: Surface treatments on quartz fiber-reinforced resin poles seem to have no significant effect on the bond strength to resin cements, except when using Duolink™ cement with sandblasted posts and using silane or primer.